MAHKAMAH KONSTITUSI DAN PENGOKOHAN DEMOKRASI KONSTITUSIONAL DI INDONESIA - Thohari, A. Ahsin (Jurnal Legislasi Indonesia, 2009)
The authorities and obligation of The Constitutional Court ofThe Republic of Indonesia based on Article 24C of the 1945Constitution are very close to the ideas and the implementationof democracy. This is related to the fact that the establishmentof The Court is intended to provide assurance of strengtheningconstitutional democracy as well as maintaning checks andbalances between branches of the state power. One of the thingsthat can be observed is after The Court’s establishment,awareness both in The House of Representatives and ThePresident are emminent whereby that laws shall be formed byobserving the norms of democracy and human rights, and shallnot be contradictory to the 1945 Constitution, as the supremelaw of the land. The House and The President shall assumethat when there is a part of the article or even the entire lawdecided by The Court is in contradictory to the 1945 Constitutionand therefore does not have any legally binding force, it isconsidered a dark political note which can reduce theircredibility in public image. This is the probably one of thesuccesses of the Constitutional court within the Indonesian statesystem.